Surgical treatment of erythroleukoplakia in lower lip with carbon dioxide laser radiation - Morosolli, Aline Rose Cantarelli; Schubert, Mark M.; Niccoli-Filho, Walter (Springer, 2006)
Erythroplakia is considered to represent a premalignant condition and is felt to be at high risk to progress to oral cancer development. When the lesion presents with red and white mucosal alterations concomitantly, the term erythroleukoplakia is used. However, in erythroleukoplakia lesions, the red or erythroplakia areas have been shown to be most likely to demonstrate dysplastic changes compared to the white hyperkeratotic areas. We present a case of patient with erythroleukoplakia involving the lower lip that was treating with carbon dioxide laser radiation (CO2) with 0.8 mm focus, 5 W, power density of 2.5 W/cm(2) in continuous. After the surgery, the vaporized surface was protected with a fibrinolisine + chloramphenicol cream. To date, after 6 months, there has been no clinically evident recurrence on the vermilion area. The functional and esthetic results observed were judged to be excellent.
Keywords: erythroplakia; erythroleukoplakia; CO2 laser radiation